Mixtures of Azepanium Based Ionic Liquids and Propylene Carbonate as High Voltage Electrolytes for Supercapacitors. (20th January 2015) - Pohlmann, S.; Olyschläger, T.; Goodrich, P.; Vicente, J. Alvarez; Jacquemin, J.; Balducci, A.
Abstract: This work provides a study of mixtures of the azepanium-based ionic liquid (IL) N-methyl, N-butyl-azepanium bis[(trifluoromethane) sulfonyl]imide (Azp14 TFSI) and propylene carbonate (PC) as electrolyte components in electrochemical double layer capacitors (EDLCs). The considered mixtures' properties were then compared to the properties of mixtures of N-butyl, N-methylpyrrolidinium bis[(trifluoromethane) sulfonyl]imide (Pyr14 TFSI) and PC in terms of viscosity, conductivity and electrochemical behavior. The mixtures' operative potentials were found to be comparable to each other, leading to operative voltages as high as 3.5 V, while retaining the low viscosities and high conductivities of PC based EDLC electrolytes.